What Drives Performance Measurement in NGOs?: A Case Study from Pakistan - Sulaiman Tahajuddin; Syed Sarmad Hasan; Abdul Wahid Mohd Kassim (Secholian Publication, 2021)
The purpose of this research paper is to understand how an NGO in Pakistan perceives the utility of its performance measurement system and thus what drives design of its PMS. The study explores the phenomenon from the perspective of NGO managers by applying qualitative approach and using critical realism to explore the issue. The paper presents the findings on the basis of an instrumental case study conducted in Pakistan. The research identifies the main objective of PMS in this NGO is to help the organization remain sustainable and its managers’ desire for legitimacy has deeply influenced the design of the PMS of the NGO. Results suggest managers perceive organizational credibility and not the accountability as the most important factor in determining its sustainability. The evidence is based on findings of a single NGO case study from Pakistan. Furthermore, the findings are based only on the perceptions of the managers of the selected organisation. Future research including perception of other stakeholders in other NGOs may help in deepening the understanding of the issue and validating the presented results. However, given that little research has been conducted within the NGO sector on drivers of performance measurement this research provides useful evidence that can be further developed. The paper specifically contributes by extending prior PM literature in an NGO environment. It has implications for the further development of legitimacy theories in the NGO sector. It raises issues about how primary focus of reporting in NGOs is shifting from accountability to showcasing.